2008
DOI: 10.1093/eurheartj/ehn363
|View full text |Cite
|
Sign up to set email alerts
|

Novel biomarkers in early diagnosis of acute myocardial infarction compared with cardiac troponin T

Abstract: Assessment of H-FABP within the first 4 h of symptoms is superior to cTnT for detection of MI, and is a useful additional biomarker for patients with acute chest pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(122 citation statements)
references
References 16 publications
7
110
0
5
Order By: Relevance
“…The interfering species tested were proteins that coexist with Myo in serum and their concentrations were selected according to their relative levels in biological fluids [40][41][42][43]. Cardiac biomarkers such as TnT and CKMB and a protein present in a biological fluids BSA were selected.…”
Section: Selectivitymentioning
confidence: 99%
“…The interfering species tested were proteins that coexist with Myo in serum and their concentrations were selected according to their relative levels in biological fluids [40][41][42][43]. Cardiac biomarkers such as TnT and CKMB and a protein present in a biological fluids BSA were selected.…”
Section: Selectivitymentioning
confidence: 99%
“…10,11 h-FABP has proven to be an early marker for the detection of myocardial infarction (MI), better than myoglobin and troponin for very early detection. [11][12][13][14][15] It also could be a sensitive marker for minor myocardial injury in patients with unstable angina (UA). 11,16,17 A novel qualitative test for the detection of h-FABP has recently been developed.…”
mentioning
confidence: 99%
“…A study of 346 patients who presented to the ED with chest pain found that PAPP-A levels were significantly higher in those patients who were diagnosed with AMI (175). In a second study that included 415 patients admitted to a cardiology unit with suspected ACS, PAPP-A levels were also found to be significantly higher in those patients with AMI although the AUC was only 0.56, suggesting that PAPP-A is unlikely to be useful as a lone diagnostic investigation for AMI (176). Further, a case control study found no significant difference in PAPP-A levels between 80 patients with STEMI and 80 healthy controls (177).…”
Section: Pregnancy-associated Plasma Protein a (Papp-a)mentioning
confidence: 98%